IMPLEMENTASI BIMBINGAN TEMAN SEBAYA DALAM KEAKTIFAN BELAJARSISWA KELAS IV SDN PARON 1 - Meisi Dian Pratiwi; Yes Matheos Lasarus Malaikosa; Sofyan Susanto (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Peer guidance is a method that provides opportunities for students to share the students’ knowledge with their peers and help their peers based on the skills the students have. Tutors are given the responsibility of helping the students in learning when they encounter difficulties in learning. The relationship between the students and their peers is closer than the teacher and the students and something that students are given to their peers usually could give a better effect than not given since the language used was easy to understand by using their own language. Peers refer to close friends or best friends. Qualitative research methodsdescribed in this article are used to know in detail the events experienced by the subjects either descriptively or thoroughly in the form of sentences. The method used was very effective for students and the teacher in which students were not bored and the teacher was not monotonous in teaching. The factor that affects peer guidance came from the same age level, which allowed children to have the same interest, talks, and activities in order to encourage friendship relationships with peers. Active learning is an activity in which students directly, intellectually, and emotionally play an important role and participate actively in learning. Active learning is an active learning system that refers to independent learning. The inhibiting factor and difficulty frequently occurred in active learning are how to solve the differences on the student characteristics.